The effects of lead exposure on immune cells in Ukrainian children - Hnidoi, Ihor; Hnida, Natalia (Annals of Mechnikov’s Institute, 2023)
Introduction. The immune system is one of the sensitive targets for the toxic effects of lead. Even low, environmentally determined doses of this pollutant can affect the state of immunity, especially in children. For the public health of even a developed country like the United States, lead poisoning of children is the longest epidemic in history. In this case, first, attention is paid to the neurotoxic effect of lead. But there is growing evidence that the immunotoxic effect of this heavy metal is also significant. There are still relatively few epidemiological studies in this direction, as evidenced by the latest review of Zheng K. et al. (2023). But it has already been proven that lead in environmentally determined doses has a predominantly immunosuppressive effect, which leads to chronicity of inflammatory processes, to an increase in the prevalence of childhood infectious diseases. There is also evidence that excessive long-term exposure to lead can lead to distortion of the immune response, which is further realized by the development of immune-mediated diseases, including bronchial asthma in children. In addition, the immunotoxic effect of lead may be associated with the ineffectiveness of vaccinations, with a decrease in antibody titer. The problem is exacerbated by the fact that in low- and middle-income countries, to which Ukraine belongs, there are no such state programs for the primary and secondary prevention of lead lesions that operate in developed countries. Studies on populations of Ukrainian children are mostly isolated and scattered. The aim of this work is to study the effect of lead by environmentally determined doses on immune cells in Ukrainian children. Material & methods. 100 random children aged 4 to 15 years were examined. The children were treated in a pediatric hospital in Odessa for various diseases. The inclusion of children in the study was carried out subject to the informed consent of the parents of the children after providing detailed information on the procedure and purpose of the work. The definition of venous blood lead concentration was by atomic-absorption spectrometry with electrothermic atomization. Indicators of the cellular link of immunity were determined in capillary blood. Results & discussion. It was obtained the verified decreasing of relative number of T-lymphocytes (p<0,05) and active T-lymphocytes (p<0,05) in the children with increasing blood lead concentration, as compared with this index in the group of children with lead level up to 4,9μg/dl. The number of B-lymphocytes (p<0,05) also decreased. With it the relative number of NK-cells (p<0,05) was increased reliably in these children. It was shown also the verified decreasing of neutrophile phagocytosis index (p<0,05) in the same children. The number of erythrocytes (p<0,05) increased. The results obtained are mainly consistent with modern literature data. Conclusions. Lead in environmentally determined doses has led to a decrease in the number of T- and B-lymphocytes in examined Ukrainian children, which can result in disturbance of the adaptive immune response process. At the same time, the number of natural killers and eosinophils increased, which may be associated with the course of diseases on the background of elevated lead levels in children, and in the future can lead either to an inadequate immune response and the development of immune-mediated diseases, or to depletion of the reserves of the immune system and the development of chronic pathology. Key words: ecology, lead, public health, children, immune cells.